An overview of human resource management practices in Bangladesh bank & foreign exchange transactions in Bangladesh: the role of foreign exchange policy department of Bangladesh bank - Hauque, Shafi Abdullah (BRAC University, 2018)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2017.